2018
DOI: 10.1177/0144598718767596
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the apparent performance characterization along with levelized cost of energy of wind power plants considering real data

Abstract: Pakistan pursued the renewable energy policy to minimize the cost of energy per kWh as well as dependence on costly imported oil. Jhimpir site is termed as wind corridor and has tremendous proven wind power potential. The site is hosted for the first installed wind power plant. The aim of paper is to investigate the performance and levelized cost of energy of a wind farm. The methodology covers assessment of wind characteristics, performance function and levelized cost of energy model. The measured mean wind s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Figure 11 shows the cumulative cost of solar generation and battery storage versus FR. From the results, it is observed that as FR increases from 60 to 77%, capital cost reduces with the cost of storage and solar generation using Equations (10), (11), and (15). It implies that with a smaller population, storage and solar generation can satisfy prosumers' load demands within a blockchain-based decentralized infrastructure.…”
Section: Variation Of Load Demand With Respect To Frmentioning
confidence: 93%
See 3 more Smart Citations
“…Figure 11 shows the cumulative cost of solar generation and battery storage versus FR. From the results, it is observed that as FR increases from 60 to 77%, capital cost reduces with the cost of storage and solar generation using Equations (10), (11), and (15). It implies that with a smaller population, storage and solar generation can satisfy prosumers' load demands within a blockchain-based decentralized infrastructure.…”
Section: Variation Of Load Demand With Respect To Frmentioning
confidence: 93%
“…However, the performance of photovoltaic (PV) technology for short and long term range with reliable information is not provided by the study in Mauritius. In Pakistan [15], LCOE is used to determine the performance of wind farms in terms of the average capacity of 34.50%, real availability of 90% and 97% of technical performance. The costs of 0.113 $/kWh and 0.040 $/kWh for 1-10 and 11-20 years are estimated from LCOE.…”
Section: Least-cost Evaluation For Decentralized Electrification In Sgmentioning
confidence: 99%
See 2 more Smart Citations
“…The maximum likelihood method is used to evaluate k and c parameters as given in (Hulio and Jiang, 2018a): …”
Section: Methodology and Datamentioning
confidence: 99%